COMMUNITY OF PHYTOPLANKTON AT KARIMUNJAWA NATIONAL PARK, JEPARA, CENTRAL JAVA - Arip Rahman; Mujiyanto Mujiyanto (Pusbindiklat - LIPI, 2013)
Karimunjawa National Park is one of nature conservation area in Jepara Regency. The development of the tourism sector in the region will affect the condition of waters. The research aimed to determine community of phytoplankton in the waters Karimunjawa. The study was conducted in April, July, October, and November 2012 with field survey. Phytoplankton samples were taken using plankton net from four locations which purposively chosen. Water quality parameters were recorded including temperature, salinity, dissolved oxygen, and nutrient. The result indicated that there were 34 species of phytoplankton which grouped into two classes, Bacillariophyceae and Diniphyceae. Diversity index ranging 0.89 and 2.3, equitability index ranging 0.67 and 0.99 and dominance index ranging 0.09 and 0.46. Based on criteria of biological indices and analysis of water quality, the condition of the waters in National Parks Karimunjawa is stable moderate. During the research does not happen certain phytoplankton species dominance.